2010
DOI: 10.1111/j.1600-048x.2010.05145.x
|View full text |Cite
|
Sign up to set email alerts
|

Do parasitic common goldeneyeBucephala clangulafemales choose nests on the basis of host traits or nest site traits?

Abstract: Conspecific brood parasitism (CBP) is an important alternative breeding strategy for gaining reproductive output in birds. While interactions between hosts and parasites and consequences of CBP to breeding success of both parties have been studied a lot, the roles of host characteristics and nest site characteristics in CBP have received less attention. We studied the relative importance of host‐related traits, such as female condition and breeding experience, and nest‐site‐related factors, such as overall nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…One might ask if the exclusion of failed nests could mask putative effects of varying breeding phenology. Most (38%) failed nests (n = 459, 1985–2008) were deserted during egg laying, likely due to conspecific brood parasitism (Paasivaara et al ). About 29% of nests were abandoned during incubation for reasons other than human disturbance or predation.…”
Section: Methodsmentioning
confidence: 99%
“…One might ask if the exclusion of failed nests could mask putative effects of varying breeding phenology. Most (38%) failed nests (n = 459, 1985–2008) were deserted during egg laying, likely due to conspecific brood parasitism (Paasivaara et al ). About 29% of nests were abandoned during incubation for reasons other than human disturbance or predation.…”
Section: Methodsmentioning
confidence: 99%
“…Milonoff et al () reported that goldeneye females that have a skip year in breeding will advance, not delay, breeding after the skip. Finally, parasitic egg laying is a common reproductive tactic employed by goldeneye females in our study population (Paasivaara et al ). We cannot exclude the possibility that sexually mature females laid parasitic eggs in years before they started normal nesting but even that tactic would have been inferior to normal nesting in terms of fitness (Åhlund and Andersson ).…”
Section: Discussionmentioning
confidence: 94%
“…Second, Cliff Swallows (Petrochelidon pyrrhonota) prefer to parasitize old rather than new nests, which may be a guarantee of its structural stability (Brown and Brown 1991). Third, probability of parasitism in nests increases with the number of previous nesting attempts and occupation rate in Common Goldeneyes (Bucephala clangula) (Paasivaara et al 2010). Fourth, Common Goldeneyes select host nests with reduced predation risk (Pöysä 2006;Pöysä et al 2010).…”
Section: Introductionmentioning
confidence: 99%